Relevance Method Habit in Muhammad Quthb's Education : Building Generation Gold in Society 5.0 - Machmud Yunus; Maragustam Siregar (al-Afkar, Journal For Islamic Studies, 2025)
Study This will explain about draft habituation in Islamic Education according to Muhammad Qutb . According to Muhammad Quthub habits , or al- tarbiyah bi al-'Adah , is considered as one of the a very important and needed approach . Method this is very effective in the educational process , both in Islamic Education and in system education others . Muhammad Quthb is one of the Islamic thinkers ( Islamic Mufakkir ) who emphasize that method role model is very important and successful in Islamic education . Therefore that , his thoughts must discussed more continue , especially outside​ room scope study This . Muhammad Qutb's Thoughts about method habits ( Uslûb Al-'Adah . Research this , using method study descriptive analysis , researcher collect data from a number of source scientific in the form of journal reputable , books , magazines furthermore researcher analyze with critical served in Good Writing framework think according to Muhammad Quth . The concept Muhammad Quthb's foundation about Islamic Education is balance between spirit , body and mind For reach Human kamil . Three unity That will achieved with get used to cognitive and psychomotor so that produce affective or morals noble students . In the era of technology , education applied character​ through digital with acceleration of time, then technology placed as means in make it easier to obtain knowledge knowledge . Teachers and students also get used to changes of the times with use digital learning in class . Because the Islamic Education curriculum is adaptive to current development .